KRIMINALISASI INSES (HUBUNGAN SEKSUAL SEDARAH) DALAM PERSPEKTIF PEMBAHARUAN HUKUM PIDANA INDONESIA - Reyhan Prima Gevari; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In the Criminal Code, the regulation regarding incest is regulated in theCriminal Code (hereinafter referred to as the Criminal Code). The article relatesto incest if the act is committed against his biological child, stepchild, adoptedchild, child under his supervision who is not yet an adult or underage as a victimof obscene acts from his parents as regulated in Article 294 paragraph (1) of theCriminal Code. In the provisions of Article 8 letter (a) of Law no. 24 Year 2004Regarding the Elimination of Domestic Violence , those who are legal subjectswho must be held accountable for their actions are individual humans orindividuals. Then in the Law No. 35 of 2004 About Child Protection . Of theseveral existing regulations, there is no regulation regarding incest committed ona consensual basis and in its current development, it turns out that there is still alegal vacuum in its criminalization.The objectives in writing this thesis are: First , to find out how thesynchronization of the law of incest in the laws and regulations in Indonesia.Second, To find out the formulation policy for the formulation of criminal normsfor incest regulation in perfecting and formulating the ideal criminal law policy.The type of research used in this research is normative legal research or itcan also be called doctrinal legal research. Normative legal research is librarylaw research . In this normative research, the author conducts research on theprinciples of law . From the results of the study, it was found that from the currentlegal protection arrangements, both in terms of Law Number 23 of 2004concerning the Elimination of Violence in Households, especially Article 46 andLaw Number 35 Years 2014 concerning child protection, especially article 81paragraph (1) . However, in these settings it has not been explicitly regulatedagainst parents and siblings as perpetrators and there are no provisionsregarding weighting of criminal threats and additional penalties for parents andsiblings as a perpetrators (crimes of incest) especially those that occur in adultsand on a consensual basis .Author's Suggestion, First, Considering how dangerous the crime of incestis committed in the family environment in relation to the legal protection ofchildren, then better in drafting legislation should be more noticed again.Keywords: Incest-Criminalization-Legal Refor